Peran Sahamiye Foundation Dalam Meningkatkan Literasi di Somaliland Melalui Aplikasi Daariz Pada Tahun 2021-2023 - Siburian, Kezia Cantik; Aisyah, Aisyah (Interdependence Journal of International Studies, 2025)
Literacy is one of the fundamental pillars of human development and social progress in a country. However, it remains a persistent challenge for developing and low-income regions such as Somaliland, which faces serious obstacles in basic education. In this context, non-state actors like the Sahamiye Foundation play a significant role through digital innovation. This study analyzes the role of the Sahamiye Foundation in promoting literacy in Somaliland through the Daariz application during the period 2021–2023. Using a qualitative descriptive method, data were collected through literature review from primary sources (official websites and the Daariz application) and secondary sources including academic journals, policy documents, and other relevant online publications. The analytical framework draws on the concept of international organizations, which encompasses three key roles: as instruments, arenas, and actors. The findings indicate that the Sahamiye Foundation strategically fulfills all three roles: as an instrument in developing educational applications and advocating for policy change; as an arena through collaborative partnerships with local institutions; and as an independent actor committed to advancing literacy without affiliation to specific political interests. Keywords: Somaliland, Literacy, Daariz, Sahamiye Foundation, International organizations